Ecological Correlates for Endemic and Threatened Amphibians in the Uluguru Nature Forest Reserve, Tanzania - Christopher, Joseph M.; Ngalason , Wilirk; Lyakurwa, John V. (Tanzania Journal of Science, 2023)
Information on habitat characteristics for endemic and threatened amphibians along the altitudinal gradient in the Uluguru Nature Forest Reserve (UNFR) is limited. We assessed habitat characteristics associated with the occurrence of endemic and threatened amphibians in the Uluguru Nature Forest Reserve between April and June 2022. Bucket pitfall traps, time-constrained audio-visual surveys, plots and opportunistic searching were used to study amphibians in 6 sites along elevational gradient from 600 m to 2100 m a.s.l. Eighteen amphibian species were recorded, thirteen of them being endemic to the Eastern Arc Mountains, two near-endemic and three widely distributed. Among the species recorded, seven are categorized as threatened as per IUCN Red List. We observed more endemic and threatened amphibians in the submontane forests (1200–1800 m) than in other sites. Negative correlations existed between temperature, canopy cover, leaf litter cover and leaf litter depth and species richness, whereas positive correlations existed between humidity and species richness. No single factor was responsible for the occurrence of endemic and threatened amphibians in the Uluguru Nature Forest Reserve. This is only a snapshot survey on the occurrence of threatened and endemic amphibians and their associated habitat features in the northern part of the Uluguru Nature Forest Reserve. A long-term monitoring of these amphibian species is recommended especially at this era of unprecedented forest loss and degradation.